Effects of twin orientation and twin boundary spacing on the plastic deformation behaviors in Ni nanowires. (1st February 2023) - Zhang, Ying; Hou, Yuxuan; Zheng, He; Zhao, Ligong; Jia, Shuangfeng; Li, Kaixuan; Peng, Huayu; Zhao, Peili; Li, Lei; Meng, Weiwei; Jiang, Renhui; Wang, Jianbo
Highlights: Effects of twin orientation ( θ ) on the Ni nanowire (NW) ductility are investigated. NW ductility with θ ∼55° increases with decreasing twin boundary (TB) spacing. In-situ TEM reveals distinct deformation behaviors in NWs with different θ . Atomistic observation reveals different roles of TB can play during deformation. The different ductility can be related with microscopic deformation mechanisms. Abstract: Spreading twins throughout nano metals has been proved to effectively mediate the mechanical behaviors in face-centered-cubic (fcc) metals. However, the experimental investigation concerning the roles of twin boundary (TB) during deformation is rarely reported. Here, with the joint efforts of in-situ nanomechanical testing and theoretical studies, we provide a systematic investigation regarding the effects of TB orientation ( θ, the angle between tensile loading direction and the normal of TB) and spacing on deformation mechanisms in Ni nanowires (NWs). As compared with single-crystalline counterparts, it is found that nano-twinned (nt) NWs with θ ∼0° exhibit limited ductility, whereas TB can serve as an effective blockage to the dislocation propagation. In contrast, in nt NWs with θ ∼20° and 55°, TB migration/detwinning induced by TB-dislocation reaction or partial dislocation movement dominates the plasticity, which contributes to enhanced NW ductility. Regarding nt NWs with θ ∼90°, dislocations are found to be able to transmit through the TBs, suggesting the limited effect of TB on the NW stretchability. Furthermore, decreasing TB spacing ( λ ) can facilitate the detwinning process and thus greatly enhance the ductility of NW with θ ∼55°. This study uncovers the distinct roles that TB can play during mechanical deformations in fcc NWs and provides an atomistic view into the direct linkage between macroscopic mechanical properties and microscopic deformation modes.